CompTIA CASP+ (CAS-004) - Gordon, Adam; Rodrick, Mike (Packt Publishing, 2023)
"Mastering CASP+ Security Architecture and Operations"" is an extensive course designed for professionals seeking to deepen their knowledge in advanced security concepts and prepare for the CASP+ exam. The course journey begins with a thorough exploration of Security Architecture, covering crucial topics like network services, segmentation, and Zero Trust models, to build a robust security foundation. As you progress, you'll delve into Security Operations, learning to manage threats, vulnerabilities, and incident responses effectively. The course then transitions into Security Engineering and Cryptography, where you'll learn about managed configurations, deployment scenarios, and hardening techniques. This section also covers cryptographic protocols, offering insights into PKI, hashing, and asymmetric algorithms. The Governance, Risk, and Compliance module further enriches your understanding by diving into risk assessments, vendor management, legal considerations, and disaster recovery planning. Throughout this journey, you'll engage in practical scenarios and discussions, synthesizing theory and application. This course not only prepares you for the CASP+ exam but also equips you with skills transferrable to real-world IT security challenges. What you will learn Analyze and implement secure network architectures. Synthesize threat management strategies. Apply vulnerability assessment methods and tools. Execute effective incident response and forensic analysis. Configure and deploy secure cloud technologies. Implement and troubleshoot cryptographic solutions. Audience This course is ideal for IT professionals, security analysts, network administrators, and anyone preparing for the CASP+ certification. It is suited for those looking to deepen their understanding of cybersecurity, improve their risk management skills, and stay updated with the latest in compliance and security architecture. About the Authors ACI Learning: ACI Learning train leaders in Cybersecurity, Audit, and Information Technology. Whether you're starting your IT career, mastering your profession, or developing your team, they're with you every step of the way. Adam Gordon: Adam Gordon, our edutainer, brings over three decades of IT instruction experience in both private and public sectors. With a remarkable record of holding more than 160 IT certifications, he has played a pivotal role in training thousands of IT professionals throughout his illustrious career. Mike Rodrick: Mike Rodrick, the host, boasts over 15 years of expertise in IT instruction. His journey includes a decade as a Microsoft Certified Trainer, and he joined the ITProTV Edutainer team in 2014. Mike's certifications include GIAC Security Essentials; Azure Fundamentals; Microsoft 365 Fundamentals; Cybersec First Responder; CompTIA ITF+, A+, Network+, Security+, Project+; MCP; MCT; MCDST; MCITP; MCTS; MCSA; MCSE; MCDBA; Certified Ethical Hacker; Certified Wireless Administrator; Certified Internet Web Professional.".
Online resource; title from title details screen (O'Reilly, viewed Decenber 19, 2023)
Keywords: Computing Technology Industry Association -- Study guides -- Examinations; Computer security -- Study guides -- Examinations; Instructional films; Nonfiction films; Internet videos